Ethnomedicine Study in Enhancing Women’s Reproductive Health - Lestari, Ririn; Mukti , Arifah Septiane; Suminar, Ratna (Genius Journal, 2024)
Objective: The aim of this research is to analyze the number and variety of uses of medicinal plants in improving reproductive health in Sukamulya Village as local community wisdom in medicine (ethnomedicine). Method: A descriptive qualitative research method using an ethnographic approach to document and analyze the practice of using medicinal plants in ethnomedicine in Sukamulya Village, Ciamis, using data collection techniques through in-depth interviews and participant observation. The research participants consisted of cadres and individuals who actively used traditional medicine. Result: Research results show that the most commonly used medicinal plants for reproductive health include fennel pulosari, cinnamon, and black cumin to reduce menstrual pain; rambusa flowers, pomegranate skin, papaya leaves, and betel leaves to reduce heavy bleeding during menstruation; bitter leaves, castor leaves, galangal, turmeric, and Mahkota dewa to regulate the menstrual cycle; and gardenia leaves and papaya leaves are often used in traditional medicine to stimulate delayed menstruation. The use of these plants is not only medicinal but also reflects cultural values ​​and traditional beliefs. Conclusion: The people of Sukamulya Village, Ciamis Regency, apparently have knowledge about medicinal plants because they usually use various types of plants as medicinal ingredients. There are around 14 species from 11 families that are known and used by the public to cure various reproductive health diseases.